Preschool teachers’ beliefs towards children with autism spectrum disorder (ASD) in Yemen - Taresh, Sahar Mohammed; Ahmad, Nor Aniza; Roslan, Samsilah; Ma'rof, Aini Marina (Multidisciplinary Digital Publishing Institute, 2020)
It is perplexing that some preschool teachers not only advise parents who have children with autism spectrum disorder (ASD) to go to religious healers, but also attribute such neurological disorders to the curse of the “evil eye” or vaccines. Although it is now the twentieth century, this behavior simply reflects the concerns of over-protective teachers and the cultural misperceptions about the actual definition of ASD. In Yemen, the term “ASD”, with its wide range of symptoms, is still ambiguous among preschool teachers. Thus, in a rather insightful piece for the education community, this study has attempted to look beneath the surface of the beliefs (religious belief–social belief–personal belief) of Yemeni preschool teachers regarding ASD. Based on the data collected from 213 teachers (20–30\31–40-~≥40 age) in the Taiz district, this study found that misconceptions specific to autism spectrum disorder were strongly evidenced among teachers who taught preschoolers. Due to personal ignorance and growing superstitions, these teachers tend to believe the society’s perceptions of ASD, thus resulting in the ignorance of scientific views. However, the mass media can increase this group’s awareness of ASD by continually assessing the inaccurate views on ASD, and correcting them. And by influencing the teachers to take a more conceptual scientific approach in serving their special needs students, furthermore, by informing preschool teachers of children’s rights in normal life in the future through providing children with an optimal chance of development by early intervention.